Content Analysis of The New York Times and The Guardian on Framing of Chinese Muslims and Islam - Naheem Gul; Adeel Shahzad (Journal of Peace, Development and Communication, 2024)
In this study, researcher has analyzed one year news stories of elite English newspapers The New York Times and The Guardian and found N=172 stories related to the conditions of Chinese Muslims and Islam in China by using different framing categories which are Anti-terrorism, Extremism, Conflict, Crime, Culture and Religion, International Efforts and Dehumanizing Act. N=63 are from The Guardian Newspaper and N=109 are from The New York Times that shows the western media has given the favorable N=109 stories to the Chinese Muslims and Islam in China. The framing theory has been adopted as a theoretical framework in this study. This content analysis of selected western newspapers, the results of framing themes represented that the western media have at least focused on the Chinese Muslims. The coding frame of international efforts showed that US is showing more concerns about the rights of Muslims in China.